2010
DOI: 10.1017/s1743921311000470
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the prestellar core mass function and link to the IMF – Herschel first results

Abstract: Abstract. We briefly review ground-based (sub)millimeter dust continuum observations of the prestellar core mass function (CMF) and its connection to the stellar initial mass function (IMF). We also summarize the first results obtained on this topic from the Herschel Gould Belt survey, one of the largest key projects with the Herschel Space Observatory. Our early findings with Herschel confirm the existence of a close relationship between the CMF and the IMF. Furthermore, they suggest a scenario according to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
(56 reference statements)
1
6
0
Order By: Relevance
“…At this stage, it is evident that sub-fragmentation of larger clumps into smaller cores is still likely underway as there is a significant population of massive fragments. However, even at this fairly early stage in their life cycle, this initial mass-spectrum appears similar to that derived for cores detected in SFCs (see e.g., Motte, André, & Neri 1998;Nutter & Ward-Thompson 2007;Enoch et al 2008;André et al 2011), and is very well approximated by a power-law at the high-mass end. Using the peaks in respective histograms for M clump and L clump , the condition…”
Section: Diagnostic Properties Of Clumpssupporting
confidence: 73%
“…At this stage, it is evident that sub-fragmentation of larger clumps into smaller cores is still likely underway as there is a significant population of massive fragments. However, even at this fairly early stage in their life cycle, this initial mass-spectrum appears similar to that derived for cores detected in SFCs (see e.g., Motte, André, & Neri 1998;Nutter & Ward-Thompson 2007;Enoch et al 2008;André et al 2011), and is very well approximated by a power-law at the high-mass end. Using the peaks in respective histograms for M clump and L clump , the condition…”
Section: Diagnostic Properties Of Clumpssupporting
confidence: 73%
“…Although B1-E does not appear filamentary, there is ample material from which dense cores may form. With higher resolution data, André et al (2011) found a threshold column density of 7 × 10 21 cm −2 for dense structures to form in Aquila via thermal instabilities along a filament at 10 K.…”
Section: Sed Fitting To Herschel Datamentioning
confidence: 98%
“…These results suggest that the CMF from the filamentary structures resembles the stellar IMF which is consistent with the gravo-turbulent scenario (see Motte et al 1998;André et al 2010). However, because prestellar cores are primarily found inside dense self-gravitating filaments, the Herschel results on nearby clouds suggest that the peak of the pre-stellar CMF may result from the pure gravitational fragmentation of filaments, independently of the cloud PDF (see André et al 2010André et al , 2011. A detailed analysis of the data is therefore needed to fully characterize the CMF/IMF relationship (e.g., environmental effects on the M * /M core conversion) and also to determine precisely the role of the turbulence, gravity, and feedback in the PDF/CMF relationship.…”
Section: Pre-existing Versus Triggered Dense Structuresmentioning
confidence: 99%